2007
DOI: 10.4161/auto.3708
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1 Regulation of Chondrocyte Apoptosis: Induction of the Autophagic Pathway

Abstract: The goal of our investigation was to explore the mechanism by which hypoxia regulates growth plate chondrocyte survival. At low O2 tension, chondrocytes were refractory to a staurosporine (i.e., apoptosis-inducing) challenge. To determine whether hypoxic survival was due to the expression of HIF-1, we evaluated the response of HIF silenced cells to staurosporine. Both, silenced cells and control chondrocytes were equally sensitive to the apoptogen challenge. To learn if resistance was mediated by the proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
120
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(129 citation statements)
references
References 21 publications
9
120
0
Order By: Relevance
“…FoxO3 has been shown to directly regulate the expression of Gabarapl1, LC3b, and Atg12l in myotubes (66). Other findings have confirmed the ability of HIF-1␣ to either indirectly regulate both BECN1/Atg6 and Atg5 (4,64) or directly bind the BNIP3 promoter (58). Interestingly, a most recent work showed that E2F1 binds the Atg1/ULK1, MAPLC3, and DRAM1 promoters, increasing their expression and regulating autophagy (44).…”
mentioning
confidence: 62%
“…FoxO3 has been shown to directly regulate the expression of Gabarapl1, LC3b, and Atg12l in myotubes (66). Other findings have confirmed the ability of HIF-1␣ to either indirectly regulate both BECN1/Atg6 and Atg5 (4,64) or directly bind the BNIP3 promoter (58). Interestingly, a most recent work showed that E2F1 binds the Atg1/ULK1, MAPLC3, and DRAM1 promoters, increasing their expression and regulating autophagy (44).…”
mentioning
confidence: 62%
“…Autophagy was also detected in growth plate, epiphyseal fusion, and osteoarthritis (Shapiro et al, 2008;van den Berg, 2011). Chondrocytes in these areas were under hypoxia, which mediated the evaluation of HIF1a expression, reduced mTOR activities, and then initiated autophagy (Bohensky et al, 2007;Shapiro and Srinivas, 2007). Under these circumstances, autophagy degraded harmful cytosol and organelles to promote the cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α could induce articular chondrocytes death through promoting cell apoptosis and autophagy (30)(31)(32). Several studies also found that cell autophagy had a protective effect on chondrocytes by inhibiting cell death (33,34). Huang et al (35) demonstrated that leptin was implicated in OA pathogenesis though promoting apoptosis and inhibiting autophagy of chondrocytes.…”
Section: Discussionmentioning
confidence: 99%